2016
DOI: 10.1016/j.chemosphere.2016.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous photochemical degradation of BDE-153 in solutions with natural dissolved organic matter

Abstract: The compound 2,2',4,4',5,5'-hexabrominated diphenyl ether (BDE-153) is an intermediate photolytic product in the degradation of highly brominated diphenyl ethers to lower brominated forms. Herein, we report the effects of two natural organic matter (NOM) sources, Suwannee River fulvic acid (SRFA) and Pony Lake fulvic acid (PLFA), on BDE-153 photolysis in water. The rate constant (k) and half-life of BDE-153 was 2.26 × 10(-2) min(-1) and 30.72 min under UV-Vis irradiation (direct photolysis at λ > 290 nm). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It was found that 3 DOM* plays an important role in the photodegradation of e.g. acetaminophen (Li et al 2017), betablockers (Wang et al 2012) and BDE-153 (Wang et al 2016). Reaction of 3 DOM* with dissolved oxygen results in the formation of 1 O 2 (McNeill & Canonica 2016), and intramolecular electron transfer between electron donors and receptors inside 3 DOM* was shown to produce reducing radical intermediates, which further react with dissolved oxygen to yield superoxide anions (O 2˙À ) (Li et al 2017).…”
Section: Effect Of Oxygen On Photolysismentioning
confidence: 99%
“…It was found that 3 DOM* plays an important role in the photodegradation of e.g. acetaminophen (Li et al 2017), betablockers (Wang et al 2012) and BDE-153 (Wang et al 2016). Reaction of 3 DOM* with dissolved oxygen results in the formation of 1 O 2 (McNeill & Canonica 2016), and intramolecular electron transfer between electron donors and receptors inside 3 DOM* was shown to produce reducing radical intermediates, which further react with dissolved oxygen to yield superoxide anions (O 2˙À ) (Li et al 2017).…”
Section: Effect Of Oxygen On Photolysismentioning
confidence: 99%
“…The preceding prediction assumes that the reaction is taking place in pure water. In more realistic treatment scenarios with water containing natural organic matter (NOM), some of the NOM may be photolyzed and produce reactive oxygen species that further contribute to the degradation of a target compound. For example, Chintalapati and Mohseni report a higher pseudo-first-order reaction rate for microcystin-LR in the presence of 2 mg/L dissolved organic carbon (DOC) than in ultrapure water. At the same time, a natural water matrix may also impede the degradation of a target compound. , Thus, the photolysis of microcystin-LR in natural water may occur at a rate that is greater or less than the average rate determined in this review.…”
Section: Critical Assessment Of Studies Reporting Microcystin-lr Degr...mentioning
confidence: 99%